Determinants of Zimbabwe’s military expenditure (1980-2003): Paper presented at ‘The Biennial Conference of the Economic Society of South Africa (ESSA) at the Elangeni Holiday Inn, Durban, South Africa, September 7-9, 2005. - Tambudzai, Zachary (2016)
A number of articles have been written on the determinants of military expenditure in developing countries, which is important given the negative effect of military expenditure on economic development. There has been no such study for Zimbabwe. This paper tries to fill this gap, by empirically testing the effects of economic factors, external factors, and geopolitical factors on Zimbabwe’s military expenditure. The empirical work is preceded by a survey of the trends in military expenditure since 1980. The paper applies a log-linear model specification based on the standard neoclassical theory (Smith, 1989; 1990; 1995) to estimate the determinants of military expenditure. It utilises OLS estimations on co-integrated variables and comes up with long run and short run (ECM) models. The empirical findings suggest that Zimbabwean military expenditure has been influenced by both external and internal factors. The significant factors include the regional wars, the military expenditure of neighbouring countries, income, the government’s domestic borrowing ability and the trade balance. The model using milex as shares of GDP data performed better than the one real milex, both in the short run and long run.